Zoroastrian rituals in context - Stausberg, Michael (Brill, 2004)
Preliminary Material /Michael Stausberg -- Contextualizing the Contexts. On the Study of Zoroastrian Rituals /Michael Stausberg -- Sequenzierung von Riten und die Ordnung der Rituale /Burkhard Gladigow -- ‘Initiations’ in Theory and in Zoroastrianism /Jan A.M. Snoek -- Meta-Theoretical Parameters for the Analysis and Comparison of Two Recent Approaches to the Study of the Yasna /Jens Kreinath -- The Art of Ritual in a Comparative Context /James W. Boyd and Ron G. Williams -- Bruch und Kontinuität in Todesritualen. Beobachtungen zu westeuropäischen und zoroastrischen Bestattungen /Dorothea Lüddeckens -- Zoroastrian and Taoist Ritual: Cosmology and Sacred Numerology /Gernot Windfuhr -- Aspects of the ‘Interiorization’ of the Sacrifice in the Zoroastrian Tradition /Antonio Panaino -- Smashing Urine: On Yasna 48.10 /Prods Oktor Skjærvø -- Les précautions rituelles et la triade du comportement /Jean Kellens -- On the Ritual Significance of the Yasna Haptaŋhāiti /Almut Hintze -- Ritual and Rituals in the Nērangestān /Philip G. Kreyenbroek -- The Yasna Ritual in Pahlavi Literature /Shaul Shaked -- Sub specie maiestatis: Reflections on Sasanian Court Rituals /Albert de Jong -- Ritual Community Meals in Ancient Iranian Religion /Anders Hultgård -- To Praise the Souls of the Deceased and the Immortal Spirits of the Righteous Ones: The Staomi or Stūm Ritual’s History and Functions /Firoze M. Kotwal and Jamsheed K. Choksy -- The Bāj-dharnā (Drōn Yašt) and its Place in Zoroastrian Rituals /Ramiyar P. Karanjia -- Fires and the Establishment of ātaš bahrāms in the Zoroastrian Tradition /Mario Vitalone -- The Ātaš nu gīt: A Reconstitutive Ritual of Recital /Sarah Stewart -- Prejudice vs. Reality. Zoroastrians and their Rituals as Seen by two 19th Century Italian Travellers /Carlo G. Cereti -- Manekji on the Religious/Ritual Practices of the Iranian Zoroastrians: An English Translation of a Passage from his Travel Report in Gujarati (1865) /Marzban Giara , Ramiyar P. Karanjia and Michael Stausberg -- Zarathustra der Priester und Prophet in der Lehre der Manichäer /Werner Sundermann -- Supernatural Intercession to Earthly Problems: Sofreh Rituals Among Shiite Muslims and Zoroastrians in Iran /Sabine Kalinock -- „O Herr, erhöre unser Monāǧāt“: Zarathustrische Traditionslinien einer persischen Gebetsgattung zwischen Indien und Iran /Beate Schmermbeck -- From Private Shrine to Pilgrim-Center: The Spectrum of Zoroastrian Shrines in Iran /Robert Langer -- Archaeological Evidence of Zoroastrian Funerary Practices /Dietrich Huff -- Kontinuität und Wandel in den Ritualen der iranischen Zarathustrier /Katayun Mazdapour -- Monday-Nights at the Banaji, Fridays at the Aslaji: Ritual Efficacy and Transformation in Bombay City /Michael Stausberg -- Abstracts /Michael Stausberg -- List of Illustrations /Michael Stausberg -- Colour Plates /Michael Stausberg.